Color illustrations and neurosurgical techniques of Serefeddin Sabuncuoglu in the 15th century - (:unkn) unknown (OXFORD UNIV PRESS INC, 2000)
SEREFEDDIN SABUNCUOGLU (AD 1385-1468?) is the author of Cerrahiyyetu'l-Haniyye (Imperial Surgery), which was written in Turkish in 1465. It was the first illustrated textbook of surgery in the Turkish medical literature, containing color illustrations of surgical procedures, incisions, and instruments. Sabuncuoglu, a pioneer of surgery, developed numerous original techniques in a variety of surgical specialties. He described surgical management of spinal trauma, epilepsy, migraine, facial palsy, hemiplegia, low back pain, cranial fracture, and hydrocephalus. The aim of this study is to describe his contributions to neurosurgery.
Keywords: Cerrahiyyetu'I-Haniyye; history of neurosurgery; Serefeddin Sabuncuoglu; 15TH-CENTURY